Correlated Li-ion migration in the superionic conductor Li10GeP2S12. Issue 18 (27th April 2021) - Yajima, Takeshi; Hinuma, Yoyo; Hori, Satoshi; Iwasaki, Rui; Kanno, Ryoji; Ohhara, Takashi; Nakao, Akiko; Munakata, Koji; Hiroi, Zenji
Abstract : A combination of single-crystal neutron diffraction experiments at low temperature and first-principles calculations revealed that a correlated migration of the densely packed Li ions governs the overall Li-ion conduction in Li10 GeP2 S12 . Abstract : An all-solid-state Li-ion secondary battery is a promising device that provides a solution to existing energy problems. However, it remains far from practical application mainly because of the lack of our basic understanding of the conduction mechanism of Li ions in Li-rich superionic conductors used as solid electrolytes in place of liquid electrolytes for conventional batteries. Herein, we studied the crystalline compound Li10 GeP2 S12 with the largest Li-ion conductivity thus far via a novel route based on a combination of single-crystal neutron diffraction experiments at low temperature and first-principles calculations, and found that a correlated migration of the densely packed Li ions governs the overall Li-ion conduction. The correlated migration mechanism provides us with guidelines on how to design efficient superionic conductors for more efficient batteries.